Odpowiedzi

2010-01-25T21:06:12+01:00
A)
x+3/2- y+2/3=-½
x+4y= 1

x+1½-y+2=-½
x=1-4y

1-4y+1½-y+2=-½
-5y=-5
y=1
x=1-4y=1-4*1=-3

y=1
x=-3

b)
2(x+3)- 3(y-2)= -4
3(x+y+2)= 2(2x+y+6)

2x+6-3y+6=-4
3x+3y+6=4x+2y+12

2x-3y=-16
-x+y=6

2x-3y=-16
y=6+x
2x-3(6+x)=-16
2x-18-3x=-16
-x=2
x=-2

y=6+(-2)=4

x=-2
y=4

c)
(x-2)2+ 2y=(x-1)2 +y -1
2x=3y

2x-4+2y=2x-2+y-1
x=1½y

2*1½y-4+2y=2*1½y-2+y-1
3y+2y-3y-y=-2-1+4
y=1

x=1½y=1½*1=1½

y=1
x=1½
2010-01-25T21:07:29+01:00
A)
x+3/2- y+2/3=-1 /2
x+4y= 1/-4y

x+3/2-y+2/3=-1/2
x=1-4y

1-4y+3/2-y+2/3=-1/2
x=1-4y

1-4y+9/6-y+4/6=-3/6
x=1-4y

2i1/6 -5y=-3/6 /-2i1/6
x=1-4y

-5y=-2i4/6 /: -5
x=1-4y

y=8/5
x=1-4y

x=1- 4 × 8/5
y=8/5

x=3/5
y=8/5


b)
2(x+3)- 3(y-2)= -4
3(x+y+2)= 2(2x+y+6)

2x + 6 -3y+6=-4
3x+ 3y +6 = 4x + 2y + 12

2x + 12 -3y=-4
3x+ 3y +6 = 4x + 2y + 12/-2y

2x + 12 -3y=-4
3x+y+6=4x+12/-12

2x + 12 -3y=-4
3x+y-6=4x

2x + 12 -3y=-4
4x=3x+y-6

2x + 12 -3y=-4







sorry ale nie mam czasu skonczyc;/